Sexual Dysfunction Related to Psychotropic Drugs: A Critical Review Part II: Antipsychotics - La Torre, A.; Conca, A.; Duffy, D.; Giupponi, G.; Pompili, M.; Grözinger, M. (Pharmacopsychiatry, 2013)
Sexual dysfunction is a potential side effect of antipsychotic drugs: this article presents a critical review of the current literature. Although many studies have been published on the subject, only some used a validated sexual function rating scale and most lacked either a baseline or placebo control or both. In addition, many of the studies on sexual dysfunction associated with antipsychotic medication are limited by other methodological flaws. However, there is consistent evidence to suggest that a large number of antipsychotic drugs adversely affect one or more of the 3 phases of sexual response (desire, arousal and orgasm). Among the antipsychotics, the so called “prolactin-raising” are probably most associated with sexual dysfunction, even if further studies to confirm this are needed: the reviewed literature shows no consistent evidence that any one antipsychotic drug has a significantly superior side effect profile over another and current information on this topic is often based on methodologically weak research. Clinicians must be aware of drug-induced sexual dysfunction, since its presence can have important consequences for clinical management and compliance.
Keywords: antipsychotic drugs; sexual dysfunction; sexual side effects; treatment-emergent sexual dysfunction